Aberrantly expressed long noncoding RNAs in the eutopic endometria of patients with uterine adenomyosis. (April 2016) - Jiang, Jian Fa; Sun, Ai Jun; Xue, Wei; Deng, Yan; Wang, Yan Fang
Abstract: Objective: Adenomyosis is a common gynecologic disease. Alterations in the eutopic endometria might play an important role in the pathogenesis of adenomyosis. Long non-coding RNA (lncRNA) represents key regulators of gene expression. Our goal was to identify differentially expressed long noncoding RNA and messenger RNA (mRNA) in the eutopic endometria of subjects with adenomyosis on a genome-wide scale. Study design: The expression level of lncRNAs and mRNAs in the eutopic endometria from women with adenomyosis and from that of normal control subjects were detected by Affymetrix Human Transcriptome Array 2.0. Bioinformatics analysis was done for further investigation. Three up-regulated and three down-regulated lncRNAs were randomly chosen for validation by quantitative real-time polymerase chain reaction. Results: A total of 165 lncRNAs and 612 mRNAs were aberrantly expressed in the eutopic endometria of subjects with adenomyosis. Pathway analysis indicated that 40 pathways corresponded to up-regulated transcripts and 39 pathways corresponded to downregulated transcripts. A list of genes that might play roles in the pathogenesis of adenomyosis were produced by comparing the difference between co-expression networks. Expression of six chosen lncRNAs was validated by quantitative real-time polymerase chain reaction. Conclusion: This study show for the first time that the lncRNA expression profile is altered in women with adenomyosis and provides new biological foundations for further mechanistic studies in this enigmatic disorder.